2013
DOI: 10.1021/ic302334x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Structural Dynamics in Noninterpenetrating Porous Coordination Polymeric Networks

Abstract: Three novel soft porous coordination polymer (PCP) or metal-organic framework (MOF) compounds have been synthesized with a new rigid ligand N-(4-pyridyl)-1,4,5,8-naphathalenetetracarboxymonoimide (PNMI) by partial hydrolysis of N,N'-di-(4-pyridyl)-1,4,5,8-naphthalenete-tracarboxydiimide (DPNI) during solvothermal reactions with Zn(II), Cd(II), and Mn(II) salts, and they are [Zn(PNMI)]·2DMA (1·2DMA, 1a), [Cd(PNMI)]·0.5DMA·5H2O (2·0.5DMA·5H2O), and [Mn(PNMI)]·0.75DMF (3·0.75DMF). The structure of 1 is based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Slightly acidic or basic solutions tend to destroy hybrid structure yielding metal salts. As was expected, methanol and ethanol tend to dissolve hybrid organic-inorganic compounds without destruction of the crystalline structure [16]. The powder X-ray diffraction analysis (see Fig.…”
Section: Resultssupporting
confidence: 62%
“…Slightly acidic or basic solutions tend to destroy hybrid structure yielding metal salts. As was expected, methanol and ethanol tend to dissolve hybrid organic-inorganic compounds without destruction of the crystalline structure [16]. The powder X-ray diffraction analysis (see Fig.…”
Section: Resultssupporting
confidence: 62%
“…Therefore, they are receiving increasing attention as they can display a wide range of interesting functional properties like dielectric [22][23][24] behavior and water sorption for heat transformation [25,26]. Furthermore, these materials can present flexible or soft porous networks, producing the third generation of porous coordination polymers [27], which are especially interesting as they can exhibit structural dynamism compared to the rigid MOFs (metal organic frameworks). This dynamic nature seems to be advantageous for the development of new materials, and can be provoked by the presence of external stimuli, as light, heat, guest removal, condensation, or reactions between the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…17 The need to prepare new coordination polymers as well as to create analogues of existing structures requires the development of new synthetic techniques to enrich the diversity and complexity of coordination polymers to achieve new functions. 18 To this end, it has long been observed that various key factors, including the coordination geometry of the metal ions and the configuration and the binding mode of the organic ligands can frequently influence the self--assembly process [19][20][21][22][23][24] which is responsible for the variation in crystal packing and overall network superstructures. 25,26 Although metal coordination compounds and polymers based on conjugated bipyridine ligands such as 4,4ʹ′--azobis(pyridine) (azopy) 27,28 have been intensively studied, their implication in the deliberate synthesis of coordination polymers and modulation thereof is an attractive perspective as the resulting materials could find application in the areas such as molecular switching.…”
Section: Introductionmentioning
confidence: 99%